Reliability and validity of the Hindi version of the Neck Pain and Disability Scale in cervical radiculopathy patients. - Agarwal, S.; Allison, Garry; Agarwal, A.; Singer, K. (Informa Healthcare, 2006)
PURPOSE: To assess the reliability and validity of the Neck Pain and Disability Scale (NPAD) translated into Hindi. METHOD: Following a pilot study to ascertain uncertainties with existing terminology in the NPAD scale, a cervical radiculopathy patient cohort (n = 63) was assessed with the translated NPAD. Reliability was assessed by regression analysis for test-retest and by item-factor and factor-total score correlations. Face validity was compared in a cross-sectional design study with an asymptomatic group (n = 38). Convergent and divergent validity were investigated by correlating the NPAD scores with the Numerical Pain Rating Scale (NPRS) for neck and arm pain, and 10 cm long VAS Activity and VAS Depression scales. RESULTS: ICC values for test-retest NPAD total and factor scores were >0.92 and R2 values >0.912. Pearson product moment correlation of item vs. factor scores varied from 0.17 - 0.91 and for factor vs. total scores 0.72 - 0.91. Differences in NPAD scores between the patient and the asymptomatic group were significant (t = 30.90, p <0.05). Convergent validity was explained when Factor 2 (minus item 20) was correlated (r = 0.67) with NPRS maximum value scores. Divergent validity was illustrated by low correlation with VAS Activity (r = 0.15) and negative correlation with VAS Depression (r = -0.80) scores. CONCLUSION: Based on the results of this study, the Hindi version of the NPAD is a reliable and valid instrument for the assessment of pain and disability in cervical radiculopathy patients.